1970
DOI: 10.1002/1097-0142(197009)26:3<666::aid-cncr2820260327>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The use of cautery in “bloodless” radical mastectomy

Abstract: Several different forms of operative procedures for carcinoma of the breast have been advocated, but radical mastectomy remains the one most often recommended. Blood loss during this procedure is frequently high, often necessitating transfusion. Unfortunately, complications of the latter have been significant and justifiably have continued to receive attention in literature. In this study, blood loss and wound healing, with and without the use of electrocautery, in radical mastectomy were evaluated from both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…As Kakos and James [11] in the 1970s suggested the use of electrocautery for breast dissection, it has been shown to decrease incision time, reduce blood loss and transfusion requirements but may be associated with increased wound complications. Ultrasonic dissection is well known in hepatic and cardiovascular surgeries and may create less thermal injuries than electrocautery.…”
Section: Tissue Dissection Techniquesmentioning
confidence: 99%
“…As Kakos and James [11] in the 1970s suggested the use of electrocautery for breast dissection, it has been shown to decrease incision time, reduce blood loss and transfusion requirements but may be associated with increased wound complications. Ultrasonic dissection is well known in hepatic and cardiovascular surgeries and may create less thermal injuries than electrocautery.…”
Section: Tissue Dissection Techniquesmentioning
confidence: 99%
“…Tissue dissection techniques in breast cancer surgery have been implicated as a major factor that influences the incidence and volume of seroma formation. Since Kakos and James 21 in the 1970s suggested the use of electrocautery for breast dissection, it has been shown to decrease incision time, reduce blood loss and transfusion requirements but may be associated with increased wound complications 21–27 . Studies comparing sharp dissection, electrocautery and ultrasonic dissection are shown in Table 1.…”
Section: Prevention and Reduction Of Seroma Formationmentioning
confidence: 99%
“…Tumescent anesthesia has been described as a successful alternative as well (10). Electrocautery is used world-wide for flap elevation and hemostasis since it was recommended by Karlos & James in 1970 (3,11).…”
Section: Discussion Discussionmentioning
confidence: 99%